2021
DOI: 10.3892/mmr.2021.12381
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of carvacrol on liver injury in type 2 diabetic db/db mice

Abstract: The present study aimed to investigate the protective effect of carvacrol on liver injury in mice with type 2 diabetes mellitus (T2DM) and to assess its potential molecular mechanism. Mice were divided into three groups (n=15/group): Non-diabetic db/m+ mice group, db/db mice group and db/db mice + carvacrol group. In the db/db mice + carvacrol group, db/db mice were administered 10 mg/kg carvacrol daily by gavage for 6 weeks. Fasting blood glucose and insulin levels were separately examined. Pathological chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…When hepatocytes are damaged, considerable amounts of AST and ALT are released into the blood. 41 In this study, the liver sections of the T2DM mice showed obvious liver injury, with structural hepatocyte changes, disorganized arrangement, and a large number of degenerative fatty vacuoles. The ALT and AST levels increased significantly ( p < 0.05), possibly due to high-fat diet-induced liver injury and elevated enzyme activity.…”
Section: Food and Function Papermentioning
confidence: 57%
“…When hepatocytes are damaged, considerable amounts of AST and ALT are released into the blood. 41 In this study, the liver sections of the T2DM mice showed obvious liver injury, with structural hepatocyte changes, disorganized arrangement, and a large number of degenerative fatty vacuoles. The ALT and AST levels increased significantly ( p < 0.05), possibly due to high-fat diet-induced liver injury and elevated enzyme activity.…”
Section: Food and Function Papermentioning
confidence: 57%
“…The supernatant was harvested as serum and stored at −80 °C for further studies. 22 Afterwards, the pancreas, kidneys, spleen, liver and interscapular brown adipose tissues were isolated and weighed immediately. The organ indexes of these isolated organs were calculated as described in eqn (5):Organ indexes = organ weight (g)/body weight (kg).…”
Section: Methodsmentioning
confidence: 99%
“…Carvacrol Diabetic C57BL/KsJ-db/db male mice-10 mg/kg Carvacrol improved blood glucose and insulin resistance of T2DM db/db mice [62] Te serum levels of TC, TG, and LDL-C were markedly reduced, whereas HDL-C levels were signifcantly increased Decreased serum ALT and AST levels Protective efects on the liver in T2DM db/db mice, which could be related to insulin, TLR 4/NF-κB, and AKT1/mTOR signaling pathways Carvone STZ-induced diabetic rats-50 mg•kg −1 Decline in the levels of plasma glucose, HbA1c, and signifcant improvement in the levels of Hb and insulin. Te reversed activities of carbohydrate metabolic enzymes, enzymic antioxidants, and hepatic marker enzymes in diabetic rats were restored to near normal level by the administration of carvone.…”
Section: Pharmacological Activity Of Monoterpenes Observedmentioning
confidence: 99%